Extra-Adrenal Adult Neuroblastoma With Aberrant Germ Cell Marker Expression: Maturation After Chemotherapy as an Important Clue to a Challenging Diagnosis. (August 2019) - Martinez-Ciarpaglini, Carolina; Machado, Isidro; Yoshida, Akihiko; Nieto, Gema; Berbegall, Ana P.; Blanquer-Maceíras, Maria Teresa; Noguera, Rosa; Ferrández, Antonio; Navarro, Samuel
Adult neuroblastoma is an extremely infrequent neoplasm, usually occurring in the adrenal medulla or in the paraspinal sympathetic ganglia, as its childhood counterpart. We report a very unusual case of a Schwannian stroma-poor adult neuroblastoma of inguinal location, showing aberrant expression of germ cell markers: SALL4 and OCT4. This aberrant marker expression, the unusual positivity for NKX2.2 and the very scattered (instead of diffuse strong) PHOX2B expression, complicated the initial diagnosis. In this case, the posttreatment histological evaluation revealed the neuroblastic nature of the lesion. Neuroblastoma maturation after treatment is an unusual finding in adults, and in this case, added an important clue for the final diagnosis. Germs cells markers expression in neuroblastoma is an interesting feature to explore and may define a subset of neuroblastomas with a different biological nature.